TRANSFER FUNCTION APPROACH TO SIGNAL DISCRIMINATION OF ULF GEOMAGNETIC DATA - Harada M.; Hattori K.; Isezaki N. (My University, 2004)
In order to study earthquake-related ULF geomagnetic field changes, it is important to discriminate the noises such as magnetic pulsations originated from solar–terrestrial interactions and artificial noises from DC-driven trains and factories. For this aim, the interstation transfer functions and wavelet transform method have been proposed and applied to the data obtained at the ULF electromagnetic sensor array at the Boso Peninsula, Japan. It is concluded that this interstation transfer function approach has a capacity for signal discrimination; that is, it shows effectiveness to eliminate noises originated from the external ionospheric sources and its secondary effects.
Keywords: ULF geomagnetic field changes; The interstation transfer functions; Wavelet transform; ULF electromagnetic sensor array; Signal discrimination